2019
DOI: 10.1016/j.ejso.2018.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Stromal characteristics are adequate prognosticators for recurrence risk in ductal carcinoma in situ of the breast

Abstract: Background: Ductal carcinoma in situ (DCIS) of the breast constitutes a heterogeneous group of nonobligate precursors for invasive breast cancer. To date, adequate risk stratification is lacking, which is presumed to result in overtreatment. We previously identified myxoid stromal architecture as a potential prognosticator for loco-regional recurrence. In the present study, we investigated the prognostic potential of stromal characteristics. Methods: Hematoxylin and eosin stained slides from 211 DCIS patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…The presence and extent of chronic inflammatory infiltrates in the periductal stroma (regardless of its architecture) was recorded in a semi-quantitative manner as previously described and was preferentially assessed at low magnification, distant from the biopsy site (if present). 18,24,25,27 Low stromal inflammation was defined as periductal stroma that is not infiltrated by lymphocytes, or that was infiltrated by few loosely arranged lymphocytes with apparent intervening stroma. 27 High stromal inflammation was defined as periductal stroma containing a chronic inflammatory infiltrate that consists of at least one lymphoid aggregate (i.e.…”
Section: Definitions For Dichotomous Histopathological Assessmentmentioning
confidence: 99%
“…The presence and extent of chronic inflammatory infiltrates in the periductal stroma (regardless of its architecture) was recorded in a semi-quantitative manner as previously described and was preferentially assessed at low magnification, distant from the biopsy site (if present). 18,24,25,27 Low stromal inflammation was defined as periductal stroma that is not infiltrated by lymphocytes, or that was infiltrated by few loosely arranged lymphocytes with apparent intervening stroma. 27 High stromal inflammation was defined as periductal stroma containing a chronic inflammatory infiltrate that consists of at least one lymphoid aggregate (i.e.…”
Section: Definitions For Dichotomous Histopathological Assessmentmentioning
confidence: 99%
“…It would therefore be interesting to investigate the prognostic value of two‐tier grading as nonhigh grade vs . high grade instead of a three‐tier grading system . This two‐tier morphological grading is corroborated by several molecular and gene expression studies that indicate a low‐grade and high‐grade pathway in breast cancer development .…”
Section: Introductionmentioning
confidence: 62%
“…45,46 It would therefore be interesting to investigate the prognostic value of two-tier grading as nonhigh grade vs. high grade instead of a three-tier grading system. 47 This two-tier morphological grading is corroborated by several molecular and gene expression studies that indicate a low-grade and high-grade pathway in breast cancer development. [48][49][50] The identification of alternative robust prognostic markers besides nuclear grade is of utmost importance, because it is likely that overtreatment of DCIS patients will continue despite the potential usage of active surveillance strategies in this limited subpopulation of "low-risk" DCIS.…”
Section: Is Active Surveillance a Noninferior Alternative?mentioning
confidence: 69%
“…For example, fibres aligned perpendicular to the tumour, termed TACS-3, are thought to facilitate a path for metastasis and have been shown to inversely correlate with disease-free survival [8]. In addition, higher fibrillar stroma content in peritumoural environment has been shown to be associated with worse disease-free survival in breast cancer [8,13]. Pancreatic ductal adenocarcinoma patients with high peri-tumoural stroma density have been shown to have better outcomes than those with intermediate or low stroma density [26].…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer, it has been observed that more mammographic dense breast tissues, containing more extensive connective tissue are associated with worse outcomes [8]. Further, it has been suggested that the amount of peri-tumoural stroma in breast cancer, quantified via tumour-to-stroma ratio, correlates with risk of local recurrence, distant metastasis, and patient survival [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%